Development of Augmented-Reality Based Adapted-Book Learning Media for Emotion Recognition for Children with Special Needs (Autism): A Visual Therapy Approach - Renalatama Kismawiyati; Rosika Novia Megaswarie; Purwanto Purwanto; Fernanda Pratama (Jurnal Ilmiah Profesi Pendidikan, 2026)
Children with Autism Spectrum Disorder (ASD) often experience considerable difficulties in recognizing and expressing emotions, which in turn affect their social–emotional skills. This study aims to develop and examine the effectiveness of an Augmented Reality (AR)–based adapted book as a visual therapy medium to support emotional recognition in children with autism. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Expert validation indicated that the media was categorized as highly valid, with an Aiken’s V score of 0.89. The implementation stage involved 10 children with autism aged 7–10 years, who participated in four 30-minute visual therapy sessions. The pretest–posttest results revealed a significant increase in the mean score of emotional recognition, from 45.2 to 76.8 (p < 0.001; d = 0.95). Moreover, 82% of the participants responded more quickly to 3D stimuli compared to conventional card media. Teachers and therapists reported that the media was engaging, user-friendly, and effective in enhancing children’s focus during therapy sessions. These findings strengthen the body of evidence that integrating AR into learning media can effectively improve the social–emotional skills of children with ASD. In practical terms, this product is feasible for use in inclusive schools and therapy centers as an innovative, interactive, and adaptive alternative for visual therapy for children with autism.